Urban Agriculture Spaces in Built Environment - Rawaa Fawzi Naom; Fatima fouad Yaseen (Iraqi Journal of Architecture and Planning, 2017)
The research had taken the concept of urban agriculture as one of the concepts that appeared within the sustainable trends in the city, and because of limited green areas, popular growth, and ongoing neglect to the urban landscape in cities. Moreover, in order to get the essential role of urban agriculture in the city, it requested the need for research in this concept.Therefore, the research problem appeared, as a knowledge need to explore the urban agriculture concept and its applying ability in order to avoid ongoing neglecting of urban landscape in the city.In order to solve the research problem, a previous literature review had been at the origin of the concept, reached to the most important vocabulary and indicators related to the special properties and the multi-use activity of the urban agriculture spaces of the city. Then the research examined the hypotheses, by a destructive and analytic study for urban agriculture projects.The results showed the connection of achieving urban agriculture within city landscape, by the contextual linking as the main characteristics, also the social and cultural uses as the most important use achieved by the presence of urban agriculture in the city landscape.Finally it had been reached to a theoretical model for urban agriculture in the city landscape.Key Words: Urban Agriculture, Landscape, spatial properties, multi-uses.